Were we used, then discarded? An analysis of the freeze on admissions in the public administration of Guinea-Bissau (Interdisciplinary Studies Journal, 2024)
The aim of this study was to analyze the decision to freeze the hiring of health professionals in the Public Administration of Guinea-Bissau, looking at the potential impacts outlined in the order that revoked the appointments of health technicians. The research used documentary and bibliographic methods. The documentary research examined the country's official and legal documents, while the bibliographic research covered scientific articles and newspaper and magazine reports on the subject. The results indicated that the justification of public spending restraint for the freeze on appointments of health professionals lacks support, given that, at the same time, councilors were being hired for positions of sovereignty, accompanied by allowances and perks. Data from the World Health Organization (WHO) showed not only a low ratio of doctors and nurses per 1,000 inhabitants in the country, but also an urgent need to increase the number of health professionals in order to improve the coverage of health services in the country. It is therefore pertinent to reconsider the situation of dismissed technicians, expand hiring and increase the availability of health services.
Keywords: Public Administration; Public Procurement; Public Health; Health Professionals; Guinea-Bissau